Efek Antibakteri dan Antibiofilm Minyak Atsiri Cendana India (Santalum album L.) Terdahap Streptococcus sanguinis dan Aggregatibacter actinomycetemcomitans (in vitro) - Tumaang, Chelsy Clarya; Binartha, Ciptadhi Tri Oka (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Periodontal disease is caused by the accumulation of bacteria in dental plaque that causes inflammation of tooth supporting tissues. Streptococcus sanguinis and Aggregatibacter actinomycetemcomitans involved in pathogenesis of periodontal disease. Prevention of periodontal disease is done by chemical plaque control using chlorhexidine. However, the use of chlorhexidine causes adverse effects. The alternative of chlorhexidine is Indian sandalwood essential oil extract. Goals: To determine the effect of Indian sandalwood essential oil in inhibiting growth and biofilm formation of Streptococcus sanguinis and Aggregatibacter actinomycetemcomitans. Methodology: 100% Indian sandalwood essential oil extract was dissolved using Tween 20 to concentrations of 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.5625%. Streptococcus sanguinis and Aggregatibacter actinomycetemcomitans were cultured for 24 hours in BHI-B at 37°C. Antimicrobial test used the microdilution method and were calculated using formula (CFU/mL). Biofilm test was carried out using the biofilm assay method incubated for 1 hour, 3 hours, and 24 hours. Biofilm assay results were calculated using microplate reader 490 nm. Results: Minimal inhibition Concentration (MIC) Streptococcus sanguinis and Aggregatibacter actinomycetemcomitans was obtained at 50%. The best concentration of Indian sandalwood essential oil in inhibiting biofilm formation of Streptococcus sanguinis was 50%. The best concentration in inhibiting Aggregatibacter actinomycetemcomitans biofilm formation for 1 hour incubation was 25%, 3 hours and 24 hours incubation was 12.5%. Conclusion: Indian sandalwood essential oil extract proved effective in inhibiting growth and biofilm formation of Streptococcus sanguinis and Aggregatibacter actinomycetemcomitans.